Seasonal Variation In Glutathione Peroxidase In Seminal Plasma Of Karan Fries (Tharparkar X Holstein Friesian) Bulls Under Tropical Climatic Conditions (Applied Biological Research, 2016)
The present study was aimed to assess the seasonal variation in glutathione peroxidase (GPx) in seminal plasma of Karan Fries (Tharparkar x Holstein Friesian) bulls. Weekly ejaculates were collected by artificial vagina (42-45°C) during winter (December to mid February), spring (mid February-April), hot dry (May-June) and hot humid(July-August) seasons. Higher concentration of GPx was observed during hot humid season (65.74±0.93 pg mL-1) than in winter (59.30± 0.60 pg mL-1), spring (60.67±0.76 pg mL-1) and hot dry (62.14±0.90 pg mL-1) seasons. The percentage of live spermatozoa decreased during hot humid season as compared to other seasons. The acrosomal integrity also decreased during hot dry (78.7±0.6%) and hot humid (74.2 ±0.6%) seasons as compared to winter (83.1±0.6%) and spring (83.4±0.5%) seasons. The supplementation of antioxidant appears essential to Karan Fries bulls during summer season under tropical climatic conditions.
Keywords: Karan Fries bulls; glutathione peroxidase; seasons